Modern approaches to development of leadership for civil service Ukraine - L.L. Kolesnik (Економіка, управління та адміністрування)
The article is devoted to the consideration of modern approaches to the development of leadership in the civil service, as one of the benchmarks for improving the efficiency of public administration, in particular, the problems of correlation of formal leadership and leadership are considered. The analysis of the basic theories of leadership is carried out and the absence of a unified theoretical approach to the interpretation of this phenomenon is established. On the basis of the unity of theory and practice, existing modern approaches to leadership development in the civil service are analyzed, and some of them are identified that can be widely used in building up and implementing leadership potential in civil service management. The main approaches to the study of leadership in modern state management are described. The necessity of existence and development of leadership in civil service for their successful functioning is proved. The author performs the comprehensive study of the development and formation of knowledge based on the modern approaches to the development of leadership in the civil service in the system of public administration and reveals these approaches in the present scientific research. At the present stage the development of our state is acute: the need for the formation of professional leaders with pronounced organizational skills, internal desire for social activity, ability to prolong the emotional, volitional, intellectual and physical intense work to achieve the goals. An important task is to create the organizational conditions for the education of the individual as a public service leader who can fully open his own ability to lead in solving professional tasks, take responsibility for consequences of their actions, to be demanding of themselves, persistent, determined and proactive. Disclosure and implementation of leadership potential of public servants are also one of the important factors of their future successful professional activities.